Antioxidant intake and mild cognitive impairment among elderly people in Klang Valley: a pilot study - Sher, Hui Wong; Roslee Rajikan,; Suzana Shahar,; Noor Aini Mohd Yusoff,; Lai, Kuan Lee; Safiyyah Abdul Aziz,; Noor Ibrahim Mohd Sakian,; Srijit Das, (Universiti Kebangsaan Malaysia, 2010)
Mild cognitive impairment (MCI) is associated with significant morbidity, especially in the development of Alzheimer’s disease and also related to nutritional factors. A pilot study was carried out to determine antioxidant intake and its relation with MCI among elderly people aged between 60 and 74 years in Klang Valley. Subjects were interviewed to obtain socio-demography data and functional status was evaluated using the Instrumental Activities of Daily Living (IADL). Data on food intake was assessed using the diet history questionnaire and food frequency questionnaire, whilst the Geriatric Depression Scale (GDS) was used to assess depression level. A combination of tests was used to assess cognitive decline, which are Mini-mental State Examination (MMSE), Clock Drawing Test (CDT), and Dementia Rating Scale (DRS). Out of 84 elderly recruited, 70 completed all parts of the study (response rate 83.3%). Mean vitamin E intake was less than the Malaysian RNI (50.0% of RNI for men and 43.0% for women). The incidence of amnestic-MCI (aMCI) was 15.7% among the respondents, while 32.8% were depressed. After adjustment for educational background, beta-carotene intake was found to be significantly (β=0.325, p<0.05) correlated to cognitive impairment based on CDT scores. The intake levels of antioxidants among subjects were unsatisfactory and beta-carotene intake was related to poor cognitive status based on CDT.